Calle14 y su enfoque político-académico como medio de circulación de saberes y conocimientos - Gómez, Pedro Pablo (Calle 14 revista de investigación en el campo del arte, 2011)
It is time to remember, in this fifth issue of Calle14, some of the characteristics of the approach that was proposed by the editorial committee since its inception, to which the academic communities of the art field have responded in a very positive way with a wide variety of articles and images, the result of their productions and artistic creations. Calle14 considers that knowledge is a means of social transformation. For this reason, so that it can be an instrument to transform subjects and collectivities, its social appropriation is necessary, a task in which the means of circulation of academic production fulfill a fundamental role. With this commitment, the editorial committee proposed that Calle14 had two versions, one printed and one digital, as two easy access routes to the contents of each issue. In addition, through the Creative Commons 2.5 Colombia license, readers are authorized to copy, distribute and publicly communicate the work. This license also states that the credits of the work must be recognized in the manner specified by the author or the licensor (but not in a way that suggests that they have their support or that they support the use made of their work); You can not use the work for commercial purposes or alter it, transform it or generate a work derived from that which constitutes the magazine in general, and each one of the articles in particular.